A Roadmap for Transforming Research to Invent the Batteries of the Future Designed within the European Large Scale Research Initiative BATTERY 2030+. Issue 17 (21st January 2022) - Amici, Julia; Asinari, Pietro; Ayerbe, Elixabete; Barboux, Philippe; Bayle‐Guillemaud, Pascale; Behm, R. Jürgen; Berecibar, Maitane; Berg, Erik; Bhowmik, Arghya; Bodoardo, Silvia; Castelli, Ivano E.; Cekic‐Laskovic, Isidora; et al.
Abstract: This roadmap presents the transformational research ideas proposed by "BATTERY 2030+, " the European large‐scale research initiative for future battery chemistries. A "chemistry‐neutral" roadmap to advance battery research, particularly at low technology readiness levels, is outlined, with a time horizon of more than ten years. The roadmap is centered around six themes: 1) accelerated materials discovery platform, 2) battery interface genome, with the integration of smart functionalities such as 3) sensing and 4) self‐healing processes. Beyond chemistry related aspects also include crosscutting research regarding 5) manufacturability and 6) recyclability. This roadmap should be seen as an enabling complement to the global battery roadmaps which focus on expected ultrahigh battery performance, especially for the future of transport. Batteries are used in many applications and are considered to be one technology necessary to reach the climate goals. Currently the market is dominated by lithium‐ion batteries, which perform well, but despite new generations coming in the near future, they will soon approach their performance limits. Without major breakthroughs, battery performance and production requirements will not be sufficient to enable the building of a climate‐neutral society. Through this "chemistry neutral" approach a generic toolbox transforming the way batteries are developed, designed and manufactured, will be created. Abstract : A long‐term research roadmap for Europe to reinventing the way we invent the batteries of the future. High throughput experiments and modeling are suggested to accelerate the finding of new battery materials and concepts and to better understand interfaces in batteries. Smart functionalizations are described such as: battery sensors and self‐healing components directly into the battery cell. Manufacturing and recycling are crosscutting perspectives permeating the road map.